Evaluasi Program Pendidikan Karakter di Toddler-KB-TK Kristen 03 Eben Haezer Salatiga - Evelina Purnama; Yari Dwikurnaningsih (Kelola: Jurnal Manajemen Pendidikan, 2021)
The purpose of this evaluative study was to give feedback on character building program that has been implemented in Toddler-KB-TK Kristen 03 Eben Haezer Salatiga in order to give a better character education and optimize its resources’ ability. This study was an evaluative study which used qualitative approach by using context, input, process, and product (CIPP) evaluation model. Data were collected through interview, questionnaire, and documentation. The subjects of this study are school’s principal, teachers, and student’s parent. The results showed that character building in Toddler-KB-TK Kristen 03 Eben Haezer Salatiga has been already well executed, but still have room for improvement. It is suggested to improve school’s member role in showing a good character exemplary for the children, increase active participation of student’s parent in building children’s character at home and community, and compose character building topics and process which is more adaptive to changes in children’s surrounding.